ANOTHER CASE OF THE MIDDLE-INCOME TRAP: CHILE, 1900–1939. (March 2022) - Couyoumdjian, Juan Pablo; Larroulet, Cristián; Díaz, Diego A.
ABSTRACT: This paper studies the evolution of the Chilean economy in the late 19 th and early 20 th century, a period when the country's convergence with developed countries came to an end. We analyse this problem in the context of the modern literature on the middle-income trap. The social, political and economic history of Chile between 1875 and 1939 is examined and the presence of most of the factors associated with the middle-income trap is found. We complement this narrative through a quantitative analysis based on the synthetic control method and argue that the process of state-led industrialisation undertaken in the country leading to the formation of CORFO was a key economic and political event. Our work presents some general lessons for developing countries facing a similar context.